Designer's guide to MAC OS X Tiger - Gamet, Jeff (Peachpit Press, 2006)
You held off on moving to Mac OS X until your bread-and-butter applications made the jump, and now you're thinking of moving up to Tiger. This book is especially geared toward designers who've become comfortable working under Mac OS X and are ready now to make the Tiger transition. Designer and prepress pro Jeff Gamet focuses on the Mac OS X Tiger features that matter most to illustrators, designers, and other graphic professionals. He explains not only how things work in Mac OS X Tiger, but how Tiger enables users to work efficiently and effectively. In chapters devoted to fonts, printing, PDF, color management, networking, the Mac's built-in design tools, and much more, readers will learn how to: * Solve the nitty-gritty issues designers confront daily * Improve production workflow and avoid common problems * Optimize, maintain, and secure your network, whether you work in a complex office environment or a small graphics studio.